2022
DOI: 10.1039/d2sc02597c
|View full text |Cite
|
Sign up to set email alerts
|

Ferroptosis promotes sonodynamic therapy: a platinum(ii)–indocyanine sonosensitizer

Abstract: Sonodynamic therapy (SDT) has unique advantages in deep tumour ablation due to its deep penetration depth, showing great preclinical and clinical potential. Herein, a platinum(II)-cyanine complex has been designed to...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 39 publications
0
38
0
Order By: Relevance
“…Recently, bipyridine-based cyclometalated Pt(II) complexes (13 and 14) (Figure 9) have been established as good sonosensitizer for cancer SDT. [64] Interestingly, the 1 O 2 generation ability of 8 was much higher on US exposure than on visible light (465 nm) exposure, as was evident from the rate constant for DPA oxidation (US: 0.00492 min À 1 vs. light: 0.00368 min À 1 ). As a result, the cytotoxicity of 14 against 4T1 cancer cells was higher under US (IC 50 ca.…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…Recently, bipyridine-based cyclometalated Pt(II) complexes (13 and 14) (Figure 9) have been established as good sonosensitizer for cancer SDT. [64] Interestingly, the 1 O 2 generation ability of 8 was much higher on US exposure than on visible light (465 nm) exposure, as was evident from the rate constant for DPA oxidation (US: 0.00492 min À 1 vs. light: 0.00368 min À 1 ). As a result, the cytotoxicity of 14 against 4T1 cancer cells was higher under US (IC 50 ca.…”
mentioning
confidence: 89%
“…Compound 14 + US treatment significantly reduced the GSH level and GPX4 expression in 4T1 cells, indicating ferroptosis as the mode of cell death. [64] The metabolomics investigation indicated that 14 on US irradiation specifically altered the glutathione metabolism in 4T1 cells. Similar to complexes 2, 4-6, complex 14 also showed notable in-vivo anticancer activity on US irradiation.…”
mentioning
confidence: 98%
“…Several recent studies have demonstrated the versatile therapeutic potential of nanomaterials that reveal induced-shear force as a sonodynamic effect causing LPO and ferroptosis. 41–44…”
Section: Ultrasoundmentioning
confidence: 99%
“…Several recent studies have demonstrated the versatile therapeutic potential of nanomaterials that reveal induced-shear force as a sonodynamic effect causing LPO and ferroptosis. [41][42][43][44] In 2021, Chen et al demonstrated synergistic tumor treatment via an SDT-based LPO mechanism to induce ferroptosis using ferumoxytol and a PpIX sonosensitizer (Fig. 4b).…”
Section: Sono-shear Force-mediated Cancer Therapymentioning
confidence: 99%
“…Sonodynamic antimicrobial chemotherapy (SACT), on the basis of sonodynamic therapy (SDT), has been established and developed as a promising alternative for microbial inactivation. SACT is a combination of ultrasound and chemotherapeutic agents termed sonosensitizers to produce highly oxidative active reactive oxygen species and ultimately achieve treatment through the removal of bacterial biofilm infections (Yang et al, 2019;Lai et al, 2022). Compared with conventional treatment modalities, SACT has superior penetration ability and high target specificity, and can overcome resistance conferred by the local microenvironment.…”
Section: Introductionmentioning
confidence: 99%